2018
DOI: 10.1364/boe.9.005205
|View full text |Cite
|
Sign up to set email alerts
|

Perception enhancement using importance-driven hybrid rendering for augmented reality based endoscopic surgical navigation

Abstract: Misleading depth perception may greatly affect the correct identification of complex structures in image-guided surgery. In this study, we propose a novel importancedriven hybrid rendering method to enhance perception for navigated endoscopic surgery. First, the volume structures are enhanced using gradient-based shading to reduce the color information in low-priority regions and improve the distinctions between complicated structures. Second, an importance sorting method based on the order-independent transpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Especially challenging is the color consistency of a distant structure at high temperatures. Researchers found that SrSi 2 O 2 N 2 , including low (5,600 K) and high (8,500 K) hue heats, may improve the WLEDs' color quality [19]- [21]. Figure 4 indicates the hue dispersion in the three mean CCTs was considerably reduced when the SrYb concentration was higher.…”
Section: Results and Analysismentioning
confidence: 99%
“…Especially challenging is the color consistency of a distant structure at high temperatures. Researchers found that SrSi 2 O 2 N 2 , including low (5,600 K) and high (8,500 K) hue heats, may improve the WLEDs' color quality [19]- [21]. Figure 4 indicates the hue dispersion in the three mean CCTs was considerably reduced when the SrYb concentration was higher.…”
Section: Results and Analysismentioning
confidence: 99%
“…In this part, the mathematical model of the passed through blue light and transformed yellow light in the triple-layer phosphor form are demonstrated in details to discuss the improvement that can be yielded from these parts. The passed through blue light and transformed yellow light for double-layer remote package with the phosphor layer thickness of h are expressed as [25], [26]:…”
Section: Results and Analysismentioning
confidence: 99%
“…Palumbo 33 conduct a systematic review of Microsoft HoloLens2 applications in healthcare since 2019, as well as the device features available to users and the software/platform/framework used, highlighting the potential and limitations of Microsoft HoloLens2 as an innovative solution for emerging research topics such as telemedicine, remote control, and motor rehabilitation. The above study shows that AR systems are currently being used successfully in oral and maxillofacial surgery, 13–17 neurosurgery, 12 cancer surgery 18,19 and internal medicine surgery 20–23 . Furthermore, experts have shown that integrating AR into medical education improves the traditional teaching model and significantly improves the immersion and interactivity of the practical training process 34,35 …”
Section: Introductionmentioning
confidence: 94%